Quality of Bronchial Biopsies for Morphology Study and Cell Sampling: A Comparison of Asthmatic and Healthy Subjects - Isabelle Labonté; Michel Laviolette; Ron Olivenstein; Jamila Chakir; Louis-Philippe Boulet; Qutayba Hamid (Canadian Respiratory Journal)
BACKGROUND: Bronchial biopsies are widely used for histopathological, primary cell culture and genetic studies, but very few reports have evaluated their quality.